2006
DOI: 10.1002/pssa.200566116
|View full text |Cite
|
Sign up to set email alerts
|

Role of interfaces on the direct tunneling and the inelastic tunneling behaviors through metal/alkylsilane/silicon junctions

Abstract: We studied the influence of the end group of the alkylsilane molecule used in Self Assembled Monolayer (SAM) in Silicon/SAM/Metal junctions. By Inelastic Electron Tunneling spectroscopy (IETS), we showed the formation of a covalent bond between the molecules and the gold electrode in the case of a thiol terminated alkylsilane. By electrical characterizations, we demonstrated that the thiol group at the interface avoids diffusion of gold into the molecule even for a 3 carbons chain. For this short molecule, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…All alkanethiol vibrational features observed previously in Aualkanethiol-Au junctions [5] also appear in the IET spectra of the SMM junctions. The observed peaks are also in agreement with those reported by Vuillaume and co-workers for metalalkanethiol-siliconoxide/silicon junctions [23,24]. The relative intensity of the different alkyl vibrational peaks are however quite different from our earlier Au-alkanethiol-Au results (e.g.…”
Section: (Some Figures In This Article Are In Colour Only In the Elecsupporting
confidence: 91%
“…All alkanethiol vibrational features observed previously in Aualkanethiol-Au junctions [5] also appear in the IET spectra of the SMM junctions. The observed peaks are also in agreement with those reported by Vuillaume and co-workers for metalalkanethiol-siliconoxide/silicon junctions [23,24]. The relative intensity of the different alkyl vibrational peaks are however quite different from our earlier Au-alkanethiol-Au results (e.g.…”
Section: (Some Figures In This Article Are In Colour Only In the Elecsupporting
confidence: 91%
“…The deposited top contact can also interact with, and chemically alter the monolayer, in addition to the above‐considered diffusion through the molecular layer. Such interaction was actually exploited to prevent diffusion in certain cases . However, for molecule‐Si hybrids the molecular dipole plays a key role, and, therefore, we wish to preserve the molecules as intact as possible.…”
Section: Resultsmentioning
confidence: 99%
“…There are some reports of reliable direct metal evaporation, but their success depends critically on specific terminal groups, such as thiol for Au, or carboxylic acid for Al . In a different approach, Hacker and coworkers observed that evaporated Au over an alkyl monolayer on Si leads to short junctions while evaporated Ag preserves the molecular tunneling barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, these tunnel junctions are also good prototypal devices to study more detailed phenomena such as: electron -molecular vibration coupling using inelastic electron tunnel spectroscopy (IETS) (Kushmerick et al, 2004, Wang et al, 2004, Petit et al, 2005, Aswal et al, 2006, Beebe et al, 2007, Long et al, 2006, current-induced local heating in a molecular junction (Huang et al, 2006), dynamical charge fluctuations using noise measurements (Clement et al, 2007) and spin-polarized transport (Petta et al, 2004, Wang andRichter, 2006). Beyond the first results, more of such experiments are now required to achieve a good agreement between a variety of different results, as well as with theoretical predictions.…”
Section: Molecular Tunneling Barriermentioning
confidence: 99%